Brain-associated alterations of Hippo pathway transcription in early maturing Atlantic salmon - Ahi, Ehsan Pashay; Verta, Jukka-Pekka; Kurko, Johanna; Ruokolainen, Annukka; Singh, Pooja; Debes, Paul Vincent; Erkinaro, Jaakko; Primmer, Craig R. (BioMed Central, 2025)
Background: Pubertal timing is a key life history trait, shaped by ecological pressures to balance reproductive success and survival. Emerging evidence suggests a link between adiposity and early maturation, potentially through hormonal signaling pathways governing puberty timing. The timing of sexual maturation in Atlantic salmon has a strong genetic basis in addition to being linked with environmental shifts and lipid reserves. A gene encoding a co-factor of the Hippo pathway, vgll3, is a major determinant of maturation timing in salmon. The Hippo pathway is known for its evolutionary conserved molecular signal role in both sexual maturation and adipogenesis. Results: In this study, we tested the expression of Hippo pathway genes in the brain of immature and mature male Atlantic salmon carrying either the early or the late maturation genotype of vgll3. We found increased brain expression of a major Hippo pathway kinase (lats1b) in individuals with early maturation genotypes of vgll3 before maturation development of testes was evident. Moreover, we found components and regulating partners of the Hippo pathway showing differential expression in brain of individuals with early and late vgll3 genotypes prior to maturation. This may suggest a role for the Hippo pathway in central nervous system processes that regulate the preparation for maturation. Conclusions: This study characterizes transcriptional changes in components of the Hippo pathway in the brain in relation to vgll3-mediated early maturation in Atlantic salmon, highlighting the potential involvement of this pathway in the central regulation of maturation prior to gonadal development.
Keywords: gene expression; Atlantic salmon; vgll3; Hippo pathway; brain; early maturation